Political Law of Nominee Agreements in Foreign Land Ownership in the Province of Bali - Razaqa Dhafin Zumirrqof, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The practice of nominee agreements, or name borrowing by foreign citizens to obtain land ownership rights in Indonesia, constitutes a form of legal circumvention that contradicts the nationality principle embedded in the Basic Agrarian Law (UUPA). This phenomenon is particularly prevalent in the Province of Bali, a region that attracts significant foreign investment and long-term residency, thereby raising critical issues in agrarian legal politics. This study employs a normative juridical method with a descriptive-analytical approach, using literature reviews of statutory regulations and court decisions. The research aims to analyze how agrarian legal politics perceives the existence of nominee agreements and the extent to which foreign citizens are afforded legal protection. The findings reveal that nominee agreements are invalid, as they contravene Article 1320 of the Indonesian Civil Code and the nationality principle, rendering them non-binding and depriving foreign citizens of legal ownership protection. However, limited legal safeguards exist through hak pakai (right of use) and hak sewa (leasehold) mechanisms under the UUPA. Comparative analysis with Vietnam and Thailand shows that both countries adopt similar restrictions but allow lawful investment access through long-term leases or condominium ownership, with Thailand imposing stricter criminal penalties for nominee arrangements. Legally, these findings underscore the need to harmonize agrarian and investment policies to close regulatory loopholes enabling nominee agreements. Practically, they highlight the urgency of strengthening BPN oversight and creating explicit prohibitions. Academically, this research contributes to the development of Indonesia’s agrarian legal politics by clarifying the normative tension between state sovereignty and economic liberalization